2011
DOI: 10.1097/ico.0b013e318228167f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calorie Restriction on Change in Lacrimal Gland With Age

Abstract: Rapid growth in the number of dry eye syndrome patients has been observed worldwide. Increased life span is considered to be at least part of the reason for this because there is a close association between aging and decreased secretory function in the lacrimal gland. Recent advances have led to a new way of thinking about intervention in the aging process. Calorie restriction (CR) is believed to retard functional decline in various organs with age. We hypothesized that CR could prevent age-related lacrimal dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…On the other hand, oxidative damage may be a key player in the pathogenesis of age-related and non-age-related dry eye [8,17,18], and our flow cytometric data were consistent with previous studies showing that 8-OHdG + cells significantly increased in both the LGs and MGs of 2Y-old mice. This may support the study suggesting that calorie restriction can be a treatment option for age-related dry eye by reducing oxidative stress [19]. In 1Y-old mice, an inconsistency was observed between the histological findings and flow cytometric data.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, oxidative damage may be a key player in the pathogenesis of age-related and non-age-related dry eye [8,17,18], and our flow cytometric data were consistent with previous studies showing that 8-OHdG + cells significantly increased in both the LGs and MGs of 2Y-old mice. This may support the study suggesting that calorie restriction can be a treatment option for age-related dry eye by reducing oxidative stress [19]. In 1Y-old mice, an inconsistency was observed between the histological findings and flow cytometric data.…”
Section: Discussionsupporting
confidence: 83%
“…37 Exercise for the treatment of dry eye disease may be a clinical application, in addition to treatment with eye drops. [38][39][40] In summary, our experiments demonstrated that tear secretion changes with exercise training in db/db mice and a daily intraperitoneal injection of AICAR in C57BL/6JJc1 mice and db/db mice. Although further investigations are needed to clarify the mechanism of the decrease in tear secretion in db/ db mice and the increase in tear secretion resulting from exercise training, these findings will improve our understanding of the mechanisms involved and may provide a potential therapeutic strategy to modulate tear secretion.…”
Section: Discussionmentioning
confidence: 55%
“…32 Regarding complementary medicine, there is some clinical trial evidence that supports the use of traditional Chinese herbs and acupuncture or related procedures in patients with DED, while preliminary investigations suggest that reducing calorie intake and body fat may be beneficial. 33,34 Management of DED may require more than 1 therapeutic modality, including treatment to reduce inflammation in addition to treatments for MGD, blepharitis, Demodex, and/or tear film instability. For each selected modality, the mechanism of action, goals of treatment, and expected treatment duration should be clearly explained in terms that can be easily understood by the patient.…”
Section: Facilitating Realistic Patient Expectations For the Treatmenmentioning
confidence: 99%